Transition-Metal-Catalyzed Enantioselective Synthesis of Indoles from 2-Alkynylanilines - Ye, Zhi-Shi; Li, Jin-Chen; Wang, Gang (Synthesis, 2022)
Optically active indole derivatives are ubiquitous in natural products and are widely recognized as privileged components in pharmacologically relevant compounds. Therefore, developing catalytic asymmetric approaches for constructing indole derivatives is highly desirable. In this short review, we summarize methods for the transition-metal-catalyzed enantioselective synthesis of indoles from 2-alkynylanilines.1 Introduction2 Aminometalation-Triggered Asymmetric Cross-Coupling Reactions/Insertion2.1 Asymmetric Cross-Coupling Reactions2.2 Asymmetric Insertion of C=O, C=C and C≡N Bonds3 Asymmetric Relay Catalysis4 Conclusion
Keywords: indoles; 2-alkynylanilines; aminometalation; cross-coupling; insertion; relay catalysis; axial chirality